PENGEMBANGAN MEDIA “PAPEPENG” (PAPAN PENJUMLAHAN DAN PENGURANGAN) PADA MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN SISWA KELAS 1 SD INP 49 PASANGGARAHAN - Aidal Fitri Munawarah; A. Husniati; Rezki Ramdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main objective of the researcher is to find out how the design of the development of the "PAPEPENG" (Addition and subtraction board) media for mathematics subjects, addition and subtraction material is reviewed from the validity of media experts, linguists, and material experts. The type of research is research and development of the 4D development model consisting of four stages of research, namely: 1) Definition; 2) Design; 3) Development; 4) Distribution. Data collection instruments are validation sheets and Lkpd. This research was conducted in class 1 of SD INP 49 Pasanggrahan. The validation results obtained from media experts were 96% in the very good category, reviewed from the Papepeng learning media for mathematics subjects to attract students' attention and as a medium that can be used repeatedly in learning. The validation results from linguists were 98% and the validation results from material experts were 94% in the very good category reviewed from examples of simple material presentations and in accordance with the curriculum. Furthermore, the results of the limited trial Lkpd distributed to students with the lowest score 1, the highest score 5, the distribution of scores shows that there are several levels measured by Lkpd. And the results of the trial use were distributed to students with the lowest score 1, the highest score 12, the distribution of scores showed that there were differences in the levels measured by the Lkpd. Based on the validation results of media experts, language experts, material experts, Lkpd limited trials, namely trials at the beginning using media as examples and trial use, namely trials using media that were made, then the Papepeng learning media for mathematics subjects was declared very good because by using physical Papepeng media it could help students easily understand the explanations given and was interesting to use during the learning process.